2015
DOI: 10.1177/1538574415614403
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Iliac Engagement Correlates With Iliac Limb Complications Following Standard EVAR

Abstract: Increased engagement in the common iliac artery following standard EVAR reduces the risks of limb complications. A clinical guide utilization of more than 70% of the total length of common iliac artery could be used as this was associated with a significantly lower rate of iliac limb complications following standard EVAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…Longer distal seal zones (>15 mm), coverage of at least 70% of the iliac seal zone, and deployment of the endograft limb within 10 mm of the internal iliac artery protect against proximal migration of the endograft limb and type Ib endoleak. 4,6,8,12,21 In this study, however, no significant changes were observed between the endoleak and control groups for seal zone length, CIA coverage, or deployment accuracy on the first postoperative CT scan. This suggests that the 1-month CT scan is good for identifying acute failures (which were not included in this study) and for defining a postoperative baseline for endograft dimensions.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…Longer distal seal zones (>15 mm), coverage of at least 70% of the iliac seal zone, and deployment of the endograft limb within 10 mm of the internal iliac artery protect against proximal migration of the endograft limb and type Ib endoleak. 4,6,8,12,21 In this study, however, no significant changes were observed between the endoleak and control groups for seal zone length, CIA coverage, or deployment accuracy on the first postoperative CT scan. This suggests that the 1-month CT scan is good for identifying acute failures (which were not included in this study) and for defining a postoperative baseline for endograft dimensions.…”
Section: Discussioncontrasting
confidence: 63%
“…Seal may be compromised by dilatation of the CIA or by limb retraction. 4,[6][7][8]12,[15][16][17][18] Expansion of the endograft limb within the CIA, displacement of the endograft limb, as well as the resulting loss of apposition, can be precisely quantified and visualized with the VIA prototype software.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kinking is a poorly understood phenomenon that has been defined as a doubling of peak systolic velocity (PSV) throughout the artery and confirmed with subsequent pressure measurement on angiography. 13 Stent graft kinking and infolding can result in flow restricting stenosis, graft thrombosis, and occlusion. Depending on their location and degree of angulation they can also result in type I endoleaks.…”
Section: Discussionmentioning
confidence: 99%